Associações entre indicadores emocionais maternos para depressão, ansiedade e estresse e problemas comportamentais de crianças com fissura labiopalatina - Silva, Francislaine da [UNESP] (2014)
Maternal emotional indicators such as depression, anxiety and stress has been considered as conditions of adversity to child development, and has been observed peculiarities and diversity of findings in relation to behavioral problems and other debilitating disorders in children across the life cycle. The present study aimed to identify and associate clinical indicators for depression, anxiety and maternal stress along with indicators of behavior problems (internalizing and externalizing) in children with cleft lip and palate. The participants were 83 pairs, mothers and their children with cleft palate of both genders, aged between three and five years old, who are in the process of treatment at the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC/USP). The instruments used were: Interview Protocol for gathering sociodemographics data, Beck Depression Inventory (BDI-II). Inventory State-Trait Anxiety (IDATE) and Inventory of Stress Symptoms for Lipp Adults (ISSL) to identify maternal emotional indicators and Child Behavior Checklist (CBCL version 1 1/2 to 5 years old), to identify behavioral problems of children. The instruments were applied as technical recommendations and in individual sessions. Data were coded according to the propositons of instruments. For the analysis, the correlation and association between maternal emotional indicators for depression, anxiety and stress and behavioral indicators of children with cleft lip and palate was performed using the Spearman p Test, the Pearson Chi-square Test and the Fisher Exact text, with the adoption of criterion of significance of p<0.05. The results indicated that children who live with mothers with clinical indicators for anxiety and depression had significantly more behavior problems, both internalizing and externalizing and total problems. Considering the stress indicators, the correlations were only observed for internalizing behaviors...